Reading the Bible with the Founding Fathers - Dreisbach, Daniel L. (Oxford University Press, 2017)
Dreisbach shows that the Bible was the most frequently referenced book in the political discourse of the American founders. Drawing on some of the most familiar rhetoric of the founding era, 'Reading the Bible with the Founding Fathers' examines the founders' diverse uses of the Bible and how scripture informed their political culture.